PENGARUH PEMANFAATAN FINACIAL TECHNOLOGY (FINTECH) DAN GAYA HIDUP KONSUMTIF TERHADAP MANAJEMEN KEUANGAN PRIBADI SISWA - Karmulloh, Muhamad Rendi; Srigustini, Astri; kurniawan, Kurniawan (LPPM UM Metro, 2026)
The rapid development of Financial Technology (FinTech) among the younger generation has made financial transactions more convenient, but it also has the potential to encourage a consumerist lifestyle that can affect students’ personal financial management. Students’ awareness of financial planning and control remains low. This study aims to analyze the influence of FinTech usage and a consumerist lifestyle on the personal financial management of students at State High School 3 Tasikmalaya, both partially and simultaneously. This study employs a quantitative approach using a survey method and an associative-causal design. The study population consists of 1,260 students, with a sample of 306 respondents selected using proportionate stratified random sampling. Data were collected via a Likert-scale questionnaire and analyzed using multiple linear regression with the aid of SPSS. The results indicate that the use of FinTech and a consumerist lifestyle, both partially and simultaneously, significantly influence students’ personal financial management. Thus, students’ personal financial management is influenced by external factors such as the use of FinTech and internal factors such as a consumerist lifestyle.